Study of Convergence of Reduced Differential Transform Method for Different Classes of Differential Equations - Seyyedeh Roodabeh Moosavi Noori; Nasir Taghizadeh (International Journal of Differential Equations)
In this work, we study the sufficient condition for convergence of the reduced differential transform method for nonlinear differential equations. The main power of this method is its ability and flexibility in solving linear and nonlinear problems properly and easily and obtain solutions both numerically and analytically. Simple approaches of reduced differential transform method and the convergence results for different classes of differential equations such as linear and nonlinear ordinary, partial, fractional, and system of differential equations are briefly discussed. Eight examples are checked to confirm convergence results as well as the strength and efficiency of the method.